2022
DOI: 10.1111/agec.12738
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of healthy and unhealthy foods by the African poor: Evidence from Nigeria, Tanzania, and Uganda

Abstract: We use national Living Standards Measurement Study (LSMS) datasets from Nigeria, Tanzania, and Uganda to examine consumption by the rural and urban poor of "unhealthy foods" (including ultra-processed foods such as sweets and sugary beverages) versus "healthy foods" beyond starchy staples (such as vegetables, beans, animal products, and fruits). Consumption of processed foods and nonstaples is often associated in policy discussion in Africa with middle-class urban consumers rather than the poor. We analyzed ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…On average, Ugandans spend nearly 50% of their total expenditure on food (Dolislager et al, 2022). This average is notably higher for the low socio-economic classes (57%) compared to the highest socio-economic class (41%).…”
Section: Accessibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…On average, Ugandans spend nearly 50% of their total expenditure on food (Dolislager et al, 2022). This average is notably higher for the low socio-economic classes (57%) compared to the highest socio-economic class (41%).…”
Section: Accessibilitymentioning
confidence: 99%
“…• Ugandan consumers spend 57% of their total expenditure on food on average (Dolislager et al, 2022).…”
Section: Import and Exportmentioning
confidence: 99%
“…This was observed when vendors explained their perception of a balanced meal where some perceived it to be the one having more than two kinds of foods regardless of the food groups, e.g., a meal consisting of stiff porridge, meat, and beans would be considered as balanced. In order to ensure accurate information, especially regarding a balanced diet, it is important for vendors to be introduced to and be familiarized with "My Plate Guidelines", which gives a proper guide in ensuring meals prepared are adequate (Cohen et al, 2017).…”
Section: Perception Of Street Food Vendorsmentioning
confidence: 99%
“…The rapid urbanization and economic improvement in urban areas of LMICs have led to a dietary transition due to an increased demand for meat, sugar‐sweetened beverages, and processed foods (Popkin, 2015; Sousa et al, 2022). Studies in low‐ and middle‐income countries such as Tanzania, Uganda, and Nigeria have shown that there is an increase in consumption of meals lacking adequate fruits and vegetables, soft drinks, and sugar‐sweetened beverages, as well as high consumption of fast foods (Dolislager et al, 2022; Pallangyo et al, 2020). Nowadays, people increasingly spend more time away from homes due to income‐generating activities and therefore have limited time to prepare meals (Hawkes et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies confirm that poor individuals have less dietary diversity than wealthier individuals [ 11 , 17 ], and people in poverty rely more on relatively inexpensive starchy staples and less on vegetables and animal foods [ 17 , 18 ]. However, studies also concluded that the poor in some areas rely more on healthy vegetables and pulses than the middle class [ 19 ].…”
Section: Introductionmentioning
confidence: 99%